A treatment for severe nodular acne: a randomized investigator‐blinded, controlled, noninferiority trial comparing fixed‐dose adapalene/benzoyl peroxide plus doxycycline vs. oral isotretinoin. (1st December 2014) - Tan, J.; Humphrey, S.; Vender, R.; Barankin, B.; Gooderham, M.; Kerrouche, N.; Audibert, F.; Lynde, C.; ,
Summary: Background: Oral isotretinoin (ISO) is the gold standard for severe nodular acne. However, as some patients are unwilling or unable to take, or are intolerant to, ISO, other options are needed. Objectives: To compare efficacy and safety of oral ISO vs. doxycycline 200 mg plus adapalene 0·1%/benzoyl peroxide 2·5% gel (D+A/BPO) in severe nodular acne over 20 weeks. Methods: This was a multicentre, randomized, controlled, noninferiority investigator‐blinded study involving 266 subjects. Results: D+A/BPO showed a significantly earlier onset of action in reducing nodules, papules/pustules and total lesions at week 2. ISO was superior in reducing nodules (95·6% vs. 88·7%), papules/pustules (95·2% vs. 79·6%) and total lesions (92·9% vs. 78·2%; all P < 0·01) at week 20. Half as many subjects for D+A/BPO compared with ISO had treatment‐related, medically relevant adverse events (33 events in 18·0% of subjects vs. 73 in 33·8% of subjects, respectively). D+A/BPO was noninferior to ISO in the intent‐to‐treat population [95% confidence interval (CI) −2·7 to 20·8 ( P = 0·13); 63·9% vs. 54·9% of subjects, respectively] and per‐protocol population [95% CI 3·9–28·6 ( P = 0·01); 74·3% vs. 58% of subjects, respectively), based on the composite efficacy/safety end point. Conclusions: D+A/BPO showed a favourable composite efficacy/safety profile compared with ISO. This combination is an alternative to ISO in patients intolerant to, or unable or unwilling to take, oral ISO, and is an option for treatment of severe nodular acne.